Epidemiological determinants in outbreaks of bitter crab disease (Hematodinium sp.) in snow crabs Chionoecetes opilio from Conception Bay, Newfoundland, Canada - Shields, Jeffrey D.; Taylor, DM; O'Keefe, PG; Colbourne, E; Hynick, E (Diseases of Aquatic Organisms, 2007)
Bitter crab disease (BCD) is caused by Hematodinium sp., an endoparasitic dinoflagellate. It lives within the hemocoeloms of snow crabs Chionoecetes opilio and Tanner crabs C. bairdi, making them unmarketable due to their bitter flavor. Two recent outbreaks of BCD have occurred in Conception Bay, Newfoundland, one from 1999 to 2000 and another from 2003 to 2005. In the earlier outbreak, prevalence was highest in juvenile and primiparous females and juvenile males. It was thought to be highest in these hosts because they molt more frequently than larger males and the disease is transmitted to newly molted crabs. In the 2003 to 2005 outbreak, the prevalence of BCD changed and was at its highest, 24 % in trapped males and 13.5 % in trawled males. This apparent shift in the dynamics of the infection between the earlier 1999 to 2000 and later 2003 to 2005 outbreaks was highly correlated with 2 factors: an increase in bottom temperatures, associated with the recent climatic warming trend in the Northwest Atlantic, and an increase in molting activity of the snow crabs due presumably to the temperature increase within Conception Bay. That is, rising temperatures occurring from 2003 to 2005 likely stimulated molting activity in snow crabs, which led to an increase in susceptible hosts in the population. Given the positive correlation between increased bottom temperature, increased molting activity, and the latest outbreak of BCD, we predict that further trends in climatic warming will enhance transmission, spreading the parasite into additional fishing areas.